Measuring the Completeness and Currency of Codified Clinical Information - Williams, J. G. (Methods of Information in Medicine, 2003)
Objectives: The paper describes how an objective score (CCscore) of the ‘completeness’ and ‘currency’ of codified clinical information relevant to the management of diabetes mellitus may be derived for individual practices.Methods: A questionnaire was developed and administered to 35 practices and statistical methods were used to test for correlation between the prevalence for diabetes mellitus and the relevant CCscoresResults: No significant correlation could be found. Conclusions: The ‘quality’ of computer-stored information varies widely across English General practices for reasons that are incompletely understood. We demonstrated how CCscores may be calibrated for different ‘views’ of ‘relevance’, ‘completeness’, and ‘currency’ and yet be consistent across practices for a given ‘view’. The potential value of this score and how it may contribute to our understanding of variation in ‘information quality’ are discussed.
Keywords: Information; standards; computerized medical records; completeness and currency of information; family practice; family practice